The Utilization of Symbolic Capital of the Museum Sonobudoyo as an Instrument of Cultural Diplomacy at the 2025 Islamic Arts’ Biennale - Luna Chantiaya Rushartono; A. Sudjud Dartanto; Tambak Sihno Purwanto (TUMATA: Journal of Arts and Cultural Management, 2026)
This research is motivated by Indonesia’s significant potential to strengthen its cultural diplomacy and economic development as strategic assets on the international stage. One way to do this is through museums as global actors within the realm of cultural diplomacy. This study aims to examine the utilization of the Sonobudoyo Museum's symbolic capital as an instrument of cultural diplomacy at the 2025 Islamic Arts Biennale. This research employs qualitative and descriptive-analytical methods, presenting detailed findings that are then analyzed using Pierre Bourdieu's theory of capital. The results indicate that there is both the formation and utilization of symbolic capital within the Sonobudoyo Museum’s involvement in the Islamic Arts Biennale 2025. Soft power emerges through the power of attraction, which can serve as a national asset in conveying diverse and compelling cultural expressions, thereby maintaining and even enhancing the museum's global image. This study concludes that the Sonobudoyo Museum's symbolic capital plays a significant role in positioning it as one of Indonesia’s global actors, particularly within the fields of arts and culture and in the context of soft diplomacy.